Pengaruh Pola Asuh Orang Tua Terhadap Kebiasaan Membaca Anak Kelompok B - Arba, Sinta Husnul Hamidiyah; Puspitasari, Ratna Nila (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
The ability to read early childhood is caused by one of the factors in the family environment. So whether or not a child is able to read letters or words depends on how the parenting style is at home. This study uses a quantitative method with the type of ex-post-facto research. The total population of group B in TK Muslimat NU 001 Ponorogo is 129 children. The sample used is 56 children taken by random sampling technique. Data collection tools using questionnaires, observations, and documentation. Data analysis in this study used simple linear regression. The significance level set is 0.05. In calculating the data, the researchers used SPSS 25 For Window and Microsoft Excel applications. The results of this study stated that the value of Sig. (2-tailed) in a simple linear regression test that is 0.00. When compared with a significance level of 0.05 (5%), the significance value of the variable is smaller than the significance level. Thus it can be concluded that Ho is rejected and Ha is accepted. This means that there is an effect of parenting variable (x) on the variable of reading habits (y) in group B at TK Muslimat NU 001 Ponorogo